Legal Protection for Notaries in the Preparation of Authentic Deeds Without Signature and Fingerprint - Hamid, Nadra Meilani (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2025)
This study examines legal protection for notaries in the preparation of authentic deeds without signatures and fingerprints, referring to Decision Number 85 K/Pid/2012 as a case study. An authentic deed is written evidence with full evidentiary force, therefore, its preparation must meet the formal requirements specified in the Notary Law (UUJN). The signature and fingerprints of the person appearing serve as verification of the identity, presence, and compliance with the parties' wishes. Failure to meet these requirements can give rise to legal issues that impact the notary's administrative, civil, and criminal liability. This study uses a normative legal method with a statutory and conceptual approach. The results indicate that notaries continue to enjoy legal protection as long as they carry out their duties in accordance with the provisions of the UUJN and the precautionary principle. There is also a gap in the norm regarding the inability of the person appearing to provide fingerprints, which has not been regulated in detail. Therefore, regulatory reform is needed to provide legal certainty for notaries.